KODE ETIK PROFESI KEGURUAN: KONSEP, IMPLEMENTASI, DAN PERLINDUNGAN HUKUM BAGI GURU DI INDONESIA - Andi Reskiya Syafira; Al Yumna Istiqamah Agus; Agus Setiawan; Takdirmin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The teaching profession plays a strategic role in developing human resources and forming national character. Teachers are not only responsible for transferring knowledge but also for instilling values, attitudes, and moral principles in students. This study employs a qualitative approach through library research to examine the teacher code of ethics conceptually and juridically, including its philosophical and legal foundations, implementation, and the four types of teacher protection mandated by Law No. 14 of 2005. The findings indicate that while the code of ethics is crucial for professional dignity, its implementation faces challenges in the digital era, necessitating strong support from professional organizations.